Fibrosarkom des Erwachsenen am Handgelenk: Ein Fallbericht - Zyluk, A.; Walaszek, I.; Grabarek, J. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2012)
Adult fibrosarcoma is a rare malignant soft-tissue neoplasm occurring in middle-aged to elderly adults. We present a case of recurrent tumor involving the wrist, which was treated by wide excision including resection of the scaphoid and radio-lunate fusion, followed by coverage of soft tissue defect with a free flap. Despite macro- and microscopic adequate tumor resection, recurrence of the neoplasm occurred at 6 months and eventually amputation of the forearm was performed.
Keywords: adult fibrosacroma